Abnormalities of the Genitourinary Tract in Female Mice Lacking GATA5 - Molkentin, Jeffery D. (American Society for Microbiology, 2000)
Members of the GATA family of transcription factors play important roles in cell fate specification, differentiation, and morphogenesis during mammalian development. GATA5, the only one of the six vertebrate GATA factor genes not yet inactivated in mice, is expressed in a pattern that overlaps with but is distinct from that of other GATA factor genes. During mouse embryogenesis, GATA5 is expressed first in the developing heart and subsequently in the lung, vasculature, and genitourinary system. To investigate the function of GATA5 in vivo, we created mice homozygous for a GATA5 null allele. Homozygous mutants were viable and fertile, but females exhibited pronounced genitourinary abnormalities that included vaginal and uterine defects and hypospadias. In contrast, the genitourinary system was unaffected in male GATA5 mutants. These results reveal a specific role of GATA5 in development of the female genitourinary system and suggest that other GATA factors may have functions overlapping those of GATA5 in other tissues.